ДЕЯКІ АСПЕКТИ ФОРМУВАННЯ СИНОПТИЧНОЇ МІНЛИВОСТІ ПОЛЯ БІОЛЮМІНЕСЦЕНЦІЇ І СКУПЧЕНЬ ПЛАНКТОНУ В ЧОРНОМУ МОРІ - Токарев, Ю. М.; Мельников, В. В.; Білокопитов, В. М.; Темних, О. В.; Бурмістрова, Н. В. (Marine Ecological Journal, 2023)
The results of studies of the bioluminescence fields, hydrological and hydrochemical characteristics of the Black Sea have been represented. It has been shown, that in the open part of the Black Sea the zones of bioluminescence fields have a higher intensity and plankton concentrations in the 9 quasistationary zones of the anticyclonic gyres, situated over the continental slope. Submergence of the surface aerated waters to the depth of 100 – 120 m takes place in these zones, which create favorable conditions for the development of many hydrobionts. Zones of feasting for many food fish are being created in these regions; during the fishing season they migrate to these zones.